Can nigella sativa and pure honey improved chemoradiotherapy effects in advanced pancreatic cancer - Kızıltan, Huriye Senay; Türkdoğan, Mehmet Kürşad; Bayır, Ayşe Güneş; Eris, Ali Hikmet; Ismaylova, Medina; Abbasi, Ahmed Nadeem; Mayadaglı, Alpaslan; Özsütçü, Nazmiye; Türkdoğan, Kürşad (MedCrave Group, 2017)
The cancer treatments cause many side effects in patients. This is more important in pancreatic cancer (PCa) than other types of cancer because the PCa patients already suffer from abdominal pain, nausea, and loss of appetite. Therefore, it is necessary to focus on new treatment ways that decrease the toxicity and increase the survival time in PCa patients. A retrospective study was performed with 20 PCa patients who had non-metastatic locally advanced inoperable PCa. Patients were divided into 2 groups. Group 1 (n=9) included patients who received chemoradiotherapy and, taken Nigella sativa(NS) and pure honey (H) (NS+H+CRT group). Group 2 (n=11) consisted of patients who treated with concurrent chemoradiotherapy (CRT or control group). The median survival time was 15months, and %11.11 of patients (n=1) had a survival time of 36months in group 1. In control group (Group 2), the median survival time was 10months. Results revealed that chemoradiotherapy supported by NS and pure honey consumption increased the survival time when used before and during treatment of PCa patients.
Keywords: Gemcitabine; Nigella sativa; Pure honey; Advanced pancreatic cancer